2018
DOI: 10.1001/jamanetworkopen.2018.6506
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient-Centered Approaches to Collect Sexual Orientation and Gender Identity Information in the Emergency Department

Abstract: Key Points Question What is the optimal patient-centered approach to collecting sexual orientation and gender identity information in the emergency department? Findings In this matched cohort study of 540 adults, sexual and gender minority patients reported significantly higher patient satisfaction with registrar form collection compared with nurse verbal collection. Non–sexual and gender minority patients, in addition to those for whom sexual orientation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 23 publications
(37 reference statements)
2
56
0
1
Order By: Relevance
“…One way that providers and staff can exhibit openness is by evaluating their own implicit bias and not assuming heterosexuality or a cisgender “norm” with their patients . Directly asking a patient with which gender they identify and what pronoun they prefer (eg, “he,” “she,” “they,” or other) and inquiring about their sexuality in a direct, nonjudgmental manner (“Are you attracted to or do you have sex with women, men, or both?” “Do you have oral, vaginal, or anal sex?” “When was the last time you had sexual intercourse?”) are simple but effective ways of demonstrating inclusiveness . For providers and staff concerned about offending cisgender/heterosexual (non‐SGM) patients who may regard such questions negatively, it may be helpful to preface such questions by stating, “To make sure that our clinic is a safe space for all of our patients, we like to ask everyone…,” thereby normalizing the process by which gender and sexual identity/activity is obtained during the clinical encounter.…”
Section: Creating a Welcoming Environment For Sgm Youthmentioning
confidence: 99%
See 2 more Smart Citations
“…One way that providers and staff can exhibit openness is by evaluating their own implicit bias and not assuming heterosexuality or a cisgender “norm” with their patients . Directly asking a patient with which gender they identify and what pronoun they prefer (eg, “he,” “she,” “they,” or other) and inquiring about their sexuality in a direct, nonjudgmental manner (“Are you attracted to or do you have sex with women, men, or both?” “Do you have oral, vaginal, or anal sex?” “When was the last time you had sexual intercourse?”) are simple but effective ways of demonstrating inclusiveness . For providers and staff concerned about offending cisgender/heterosexual (non‐SGM) patients who may regard such questions negatively, it may be helpful to preface such questions by stating, “To make sure that our clinic is a safe space for all of our patients, we like to ask everyone…,” thereby normalizing the process by which gender and sexual identity/activity is obtained during the clinical encounter.…”
Section: Creating a Welcoming Environment For Sgm Youthmentioning
confidence: 99%
“…are simple but effective ways of demonstrating inclusiveness. 16,32,35,37 For providers and staff concerned about offending cisgender/heterosexual (non-SGM) patients who may regard such questions negatively, it may be helpful to preface such questions by stating, "To make sure that our clinic is a safe space for all of our patients, we like to ask everyone…," thereby normalizing the process by which gender and sexual identity/activity is obtained during the clinical encounter. Alternatively, SGM status may be acquired via patient intake form, a method that was found to be preferred by SGM adults in the emergency room setting, while non-SGM adults were comfortable with either approach.…”
Section: Intersexmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying an efficient and culturally sensitive method for collecting SOGI information in the ED is particularly relevant because, as the authors note, it is a frequent source of care for uninsured and underinsured patients and SGMs are at greater risk for being uninsured compared with their cisgender and heterosexual counterparts. 4,5 The authors found SGM patients reported significantly greater satisfaction when SOGI information was collected nonverbally compared with verbally. Why does this matter?…”
mentioning
confidence: 95%
“…8 Precision-based, or patient-centered, approaches have shown the efficacy of treating the whole patient and not just the symptoms or the disease. Haider and colleagues 4 showed the importance of a patient-centered approach in identifying optimal and evidence-based methods to collect patient SOGI information.…”
mentioning
confidence: 99%